Malaysia's economic success story and challenges - Koen, Vincent (OECD Economics Department Working Papers, 2017)
Malaysia has sustained over four decades of rapid, inclusive growth, reducing its dependence on agriculture and commodity exports to become a more diversified, modern and open economy. GDP per capita is now higher than in a number of OECD economies, while poverty and income inequality have declined considerably. Growth has also been remarkably resilient in the face of external shocks. Going forward, the Malaysian government's 11th Malaysia Plan (2016-20) emphasises the need for greater inclusiveness. Continued, gradual fiscal consolidation is a key policy priority, building on earlier energy and food subsidy rationalisation and on the introduction of a goods and services tax. So is continued prudent monetary and financial policy. Further reforms are needed for Malaysia to become a high-income nation around 2020: productivity growth needs to be reinvigorated through various structural reforms while growth needs to become more inclusive